KEMUNCULAN KEMAMPUAN LITERASI PERMULAAN ANAK USIA DINI - Nor Amalia Abdiah; Noranisa (IAI DARUL ULUM KANDANGAN, 2023)
Majority of parents assumes that reading, writing, and counting as a child's literacy ability, therefore they measure the success of PAUD with the success of children being able to read or count in the early childhood. However, literacy is not limited to the ability to read, write and count, but also emergent literacy which refers to what children learn before they are able to read and write. Therefore, emergent literacy is the foundation for higher literacy skills including reading, writing and more complex language comprehension. The method used in this study is descriptive statistics, through filling out a Guttman scale containing 16 statements filled out by pre-school teachers/parents. The results obtained from this study is high score of emergent literacy due to the influence of active social interaction by children with their peers, and other adults, which proves that activeness in social interaction will further improve early childhood literacy.